2012
DOI: 10.1111/exd.12022
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin M/E knockdown by lentiviral delivery of shRNA impairs epidermal morphogenesis of human skin equivalents

Abstract: The protease inhibitor cystatin M/E (CST6) regulates a biochemical pathway involved in stratum corneum homeostasis, and its deficiency in mice causes ichthyosis and neonatal lethality. Cystatin M/E deficiency has not been described in humans so far, and we did not detect disease-causing mutations in the CST6 gene in a large number of patients with autosomal recessive congenital ichthyosis, who were negative for mutations in known ichthyosisassociated genes. To investigate the phenotype of CST6 deficiency in hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…We have previously described the use of in vitro human skin equivalents to study skin biology and inflammation [20,21,[24][25][26][27] . We here took a transgenic approach to selectively overexpress hBD2 or hBD3, using lentiviral gene delivery in primary keratinocytes as we have described previously [25] .…”
Section: Effect Of Lentiviral Delivery Of Hbd2 and Hbd3 On 3-dimensiomentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously described the use of in vitro human skin equivalents to study skin biology and inflammation [20,21,[24][25][26][27] . We here took a transgenic approach to selectively overexpress hBD2 or hBD3, using lentiviral gene delivery in primary keratinocytes as we have described previously [25] .…”
Section: Effect Of Lentiviral Delivery Of Hbd2 and Hbd3 On 3-dimensiomentioning
confidence: 99%
“…We here took a transgenic approach to selectively overexpress hBD2 or hBD3, using lentiviral gene delivery in primary keratinocytes as we have described previously [25] . We used the involucrin promoter to drive hBD expression only in the stratum granulosum of the epidermis.…”
Section: Effect Of Lentiviral Delivery Of Hbd2 and Hbd3 On 3-dimensiomentioning
confidence: 99%
“…Immunohistochemical analysis was performed as described earlier . Tissues were fixed in 4% paraformaldehyde and embedded in paraffin.…”
Section: Methodsmentioning
confidence: 99%
“…The critical cystatin E/M target seems to be cathepsin L/V, as simultaneous ablation of cathepsin L rescued cystatin E/M deficient mice lethality (Zeeuwen et al, 2010). Based on the deletion of cystatin E/M in a reconstructed human skin model, which showed an impaired epidermis development instead of ichthyosis-like features, it was suggested that the inhibitor might be critical also for humans (Jansen et al, 2012). Moreover, the transglutaminase activity is also dependent on release of cathepsins from lysosomes and Ca 2+ from endoplasmic reticulum and thereby on cystatin E/M cathepsin L/V axis.…”
Section: Cornificationmentioning
confidence: 99%
“…However, calpain-1-dependent LMP, which is triggered after tight envelope formation to prevent uncontrolled degradation, occurs from unknown reason Eckhart et al, 2013;Costanzo et al, 2015). Anyhow, dysregulation of proteases and their inhibitors in the skin might be related to development of various diseases, such as Netherton syndrome, Papillon-Lefevre syndrome as well as impaired skin barrier function (Zeeuwen, 2004;Cheng et al, 2009;Zeeuwen et al, 2009;Jansen et al, 2012).…”
Section: Cornificationmentioning
confidence: 99%